Right atrial tuberculoma: a diagnosis too late - Ngow, Harris Abdullah; Wan Mohd Nowalid, Wan Khairina (Via Medica, 2011)
Solitary intra-cardiac cavity tuberculoma is extremely rare and often only diagnosed during a post-mortem. We report a case of right atrial tuberculoma causing right atrial outflow tract obstruction in an immune-compromised man. The diagnosis of cardiac tuberculoma was made through the detection of mycobacterium tuberculosis DNA by tuberculosis-polymerase chain reaction in the pericardial fluid. The patient succumbed five days after admission but an autopsy was refused by his family.